Eagles: built for the hunt - Gange, Tammy; Gagne, Tammy (London: Raintree, 2016)
WILDLIFE (CHILDREN'S / TEENAGE). Have you ever had someone say you had an eagle eye? This saying comes from the fact that eagles have excellent eyesight. This an eagle can spot prey from up to 1 mile away! Eagles also have sharp talons and can fly at jaw-dropping speeds to capture prey. Readers will learn about what makes eagles such deadly predators, from their hunting styles to what they like to eat. This title includes fun facts and an amazing but true section will thrill readers and give them a closer look at the lives of these awesome creatures. Ages 7+
Includes bibliographical references and index.
Ages 7+